Expansive open-door laminoplasty secured with titanium miniplates is a good surgical method for multiple-level cervical stenosis - Yeh, Kuang-Ting (J Orthop Surg Res, 2014)
BACKGROUND: Laminoplasty is an effective procedure for treating cervical spondylotic myelopathy (CSM). Little information is available regarding the surgical outcomes of expansive open-door laminoplasty (EOLP) when securing with titanium miniplates without bone grafting. This study is aimed to elucidate the efficacy of and problems associated with EOLP secured with titanium miniplates without bone grafting, thereby enhancing future surgical outcomes. METHODS: This is a retrospective study. The study participants comprised 104 patients who underwent cervical EOLP secured with titanium miniplates without bone graft for CSM treatment between August 2005 and March 2011. The clinical results were evaluated based on the Japanese Orthopedic Association (JOA) and Nurick scores. The radiographic outcomes were determined based on plain film and magnetic resonance imaging findings, which were assessed and compared. RESULTS: Lateral cervical spine X-rays exhibited improvement in the Pavlov ratio of the spinal canal at 1 day postoperation, and this ratio did not change at 1 year postoperation. The mean cervical curvature from C2 to C7 decreased 0.21° ± 10.09° and the mean cervical range of motion was deteriorated by 35% at 12 months (P < 0.05). The Nurick score improved from 3.19 ± 1.06 to 0.92 ± 1.32 (P < 0.05). The mean JOA recovery rate was 75% ± 21.1% at 1 year. The mean level of postoperative neck pain at 3 months was 3.09 ± 2.31, as determined using the visual analogue scale (VAS). Increased age, concomitant thoracolumbar stenosis, depression disorder, and preexisting myelomalacia negatively affected the JOA recovery rate (P < 0.05). A decreased preoperative Nurick score and superior sensory function in the upper extremities were powerful predictors of an enhanced JOA recovery rate. The postoperative complications involved hematoma formation 0.9%, reversible C5 nerve palsy 2.8%, and moderate to severe neck pain (VAS ≥ 4) 42%. No cases of lamina closure or collapse were observed. CONCLUSION: EOLP secured with titanium miniplates without bone grafting is a safe and effective surgical method for treating most patients with CSM.